Biodegradable all-cellulose composite membranes for simultaneous oil/water separation and dye removal from water. (15th December 2020) - Ao, Chenghong; Zhao, Jiangqi; Li, Qingye; Zhang, Jian; Huang, Bingxue; Wang, Qunhao; Gai, Jinggang; Chen, Zhenming; Zhang, Wei; Lu, Canhui
Graphical abstract: Highlights: A versatile membrane is produced by a cost-effective and green method. All the components of the membrane are biodegradable. Cellulose gel coating is essential for the separation of oil/water emulsion. Structural stability and dye removal efficiency are enhanced by citric acid. One-step separation of oils and organic dyes from water is realized. Abstract: While of enormous scientific interests, the super-wetting materials capable of one-step separation of oils and dyes from water are rare on the market. Besides, the disposal of the used materials themselves is still a challenge, mainly ascribed to their non-biodegradation. Herein, we report an all-cellulose composite membrane that can simultaneously remove oil and dye from water. The membrane was fabricated via a simple dip-coating process during which the filter paper was coated by a cellulose hydrogel layer. This cellulose hydrogel coating was discovered to play an essential role in the separation of oil/water emulsion. Meanwhile, the incorporation of citric acid remarkably improved the mechanical and adsorption properties of the membrane as it served as both the crosslinking agent and the active species for methylene blue adsorption. This work demonstrated a new strategy on the development of fully biodegradable materials for both high-efficiency oil/water separation and dye removal.